Malignancies Presenting with Alveolar Infiltrates: Diagnostic Pitfalls, Radiologic Clues, and Clinical Patterns - Mathavan, Akshay; Mathavan, Akash; Rojas, Olga R. G.; Ataya, Ali (Seminars in Respiratory and Critical Care Medicine, 2025)
Alveolar infiltrates are a common but nonspecific radiologic finding that can obscure the diagnosis of underlying malignancy. While infections and inflammatory processes are typical considerations, a subset of cancers, both primary and secondary, can present with alveolar opacities that mimic these benign conditions. This review synthesizes the spectrum of neoplastic diseases that manifest with an alveolar radiographic pattern, focusing on both primary pulmonary malignancies (such as lepidic-predominant adenocarcinoma, invasive mucinous adenocarcinoma, and pulmonary lymphoma) and select metastatic solid tumors (notably renal cell carcinoma, gastrointestinal cancers, melanoma, and breast cancer) that exhibit a nondestructive, airspace-filling growth. We also describe secondary and paraneoplastic processes, including immune-mediated pneumonitis, eosinophilic pneumonia, leukemic pulmonary hemorrhage, diffuse alveolar hemorrhage, and secondary alveolar proteinosis, that can similarly produce alveolar opacities in the setting of malignancy. Each entity is discussed with emphasis on its clinical presentation, diagnostic approach, imaging features, and distinguishing characteristics. Radiographic findings and other diagnostics are integrated to highlight the importance of early recognition and appropriate investigation. Distinguishing malignant from infectious or inflammatory causes of alveolar disease remains challenging but critical, as misdiagnosis can lead to inappropriate treatment or delays in therapy. Summary tables are provided to support practical clinical differentiation and management. By improving recognition of neoplastic causes of alveolar infiltrates, clinicians may better tailor diagnostic workups and initiate appropriate treatment strategies.
Keywords: alveolar infiltrates; alveolar-pattern lung involvement in cancer; malignancy-associated lung disease; pulmonary complications of malignancy